Recent advances in the removal of radioactive iodine by bismuth-based materials - Hao, Yuxun; Tian, Zhenjiang; Liu, Chuanying; Xiao, Chengliang (Frontiers in Chemistry, 2023)
Nowadays, the demand for nuclear power is continue increasing due to its safety, cleanliness, and high economic benefits. Radioactive iodine from nuclear accidents and nuclear waste treatment processes poses a threat to humans and the environment. Therefore, the capture and storage of radioactive iodine are vital. Bismuth-based (Bi-based) materials have drawn much attention as low-toxicity and economical materials for removing and immobilizing iodine. Recent advances in adsorption and immobilization of vapor iodine by the Bi-based materials are discussed in this review, in addition with the removal of iodine from solution. It points out the neglected areas in this research topic and provides suggestions for further development and application of Bi-based materials in the removal of radioactive iodine.